The Fanconi anaemia pathway: new players and new functions - Ceccaldi, Raphael; Sarangi, Prabha; D'Andrea, Alan D. (Nature reviews. Molecular cell biology, 2016)
Key Points The Fanconi anaemia pathway comprises 19 Fanconi anaemia proteins (FANCA to FANCT) and many associated proteins. Germline inactivation of any of the Fanconi anaemia genes causes the disease Fanconi anaemia, which is a genetic disorder characterized by bone marrow failure and predisposition to cancer. The Fanconi anaemia pathway intersects with many other repair processes to respond to interstrand crosslink (ICL) DNA lesions. Studies in the Xenopus egg extract system have provided important insights into the molecular mechanisms of ICL repair through the Fanconi anaemia pathway. Fanconi anaemia proteins have other functions in addition to ICL repair. Fanconi anaemia proteins, notably FANCD2, have crucial roles in replication fork protection and cytokinesis. The Fanconi anaemia pathway, together with other repair processes such as homologous recombination, nucleotide excision repair, translesion synthesis and alternative end joining, forms an intricate network beyond the core ICL repair components to repair diverse DNA lesions. Proteins of the Fanconi anaemia pathway are master regulators of genomic integrity through their interactions with other DNA repair pathways to repair interstrand crosslinks, stabilize replication forks and regulate cytokinesis. The Fanconi anaemia pathway repairs DNA interstrand crosslinks (ICLs) in the genome. Our understanding of this complex pathway is still evolving, as new components continue to be identified and new biochemical systems are used to elucidate the molecular steps of repair. The Fanconi anaemia pathway uses components of other known DNA repair processes to achieve proper repair of ICLs. Moreover, Fanconi anaemia proteins have functions in genome maintenance beyond their canonical roles of repairing ICLs. Such functions include the stabilization of replication forks and the regulation of cytokinesis. Thus, Fanconi anaemia proteins are emerging as master regulators of genomic integrity that coordinate several repair processes. Here, we summarize our current understanding of the functions of the Fanconi anaemia pathway in ICL repair, together with an overview of its connections with other repair pathways and its emerging roles in genome maintenance.